Perceptions of touristification according to place of residence in the destination: the case of Malaga. - Almeida-García, Fernando; Cortés-Macías, Rafael; Mena Navarro, Alfredo; Coll-Ramis, Miquel Ángel (Asociación de Geógrafos Españoles, 2023)
A novel research is carried out on the relationships between tourism governance, touristification and the perception of the impacts generated in a consolidated urban destination such as Malaga. It proposes a measure of touristification and its impacts in terms of the spatial distribution of residents. To this end, 450 residents of the municipality were surveyed and 15 semi-structured interviews were conducted. Factor analysis and qualitative content analysis were applied. The results show the link between governance and touristification and how this affects perceptions of economic, social and environmental impacts and place identity. In particular, place of residence (centre/periphery) influences perceptions related to touristification.
Percepciones de la turistificación según lugar de residencia en el destino: el caso de Málaga
Keywords: Turismo - Aspectos sociales; Turismo - Málaga - Opinión pública; Destino urbano; Residentes; Impactos turísticos; Urban destination; Residents; Turism impacts